The Application Of Warm Lemongrass Tea To Reduce Menstrual Pain In Adolescent Girls Through The Application Of Dorothea Orem's Self Care Theory At State High School 05 In Bengkulu City In 2025 - Sari, Ayu Permata; Susanti, Meri Epriana (Utami Publisher, 2026)
Dysmenorrhea is one of the most common menstrual disorders experienced by adolescent girls and often reduces their activity and quality of life. Menstrual pain can be treated with non-pharmacological therapies, one of which is consuming warm lemongrass tea, which contains essential oils that have anti-inflammatory and analgesic properties. This study aims to apply warm lemongrass tea therapy in reducing menstrual pain in adolescent girls using an application. The research design used a case study with a qualitative approach. There were two participants in this study, both adolescent girls at SMAN 05 Kota Bengkulu who experienced moderate menstrual pain (4–6). Data collection was conducted through interviews, observations, and physical examinations over three days. The intervention provided was warm lemongrass tea accompanied by self-care education based on Orem's concept, which includes universal self-care requirements, developmental self-care requirements, and health deviation. The results showed a decrease in pain intensity in both respondents after receiving warm lemongrass tea therapy. Respondents were also able to understand how to make and use lemongrass tea as an independent effort to reduce menstrual pain. This intervention proved to be effective as a non-pharmacological complementary therapy and was in line with the application of Orem's theory in increasing adolescent self-care independence.